Vulnerability to sexually transmitted infections of women who have sex with women - Andrade, Juliane; Ignácio, Mariana Alice Oliveira [UNESP]; de Freitas, Ana Paula Freneda [UNESP]; Parada, Cristina Maria Garcia de Lima [UNESP]; Duarte, Marli Teresinha Cassamassimo [UNESP] (FapUNIFESP (SciELO), 2020)
The scope of this study was to assess the degree of vulnerability to sexually transmitted infections of women who have sex with women. It involved a cross-sectional study of 150 women between 2015 and 2017. A structured questionnaire was applied, and a gynecological examination was performed to diagnose Chlamydia trachomatis, Neisseria gonorrhoeae, Trichomonas vaginalis and papillomavirus. Blood tests were conducted to detect HIV, hepatitis B and syphilis. The outcome variable was sexual infection and the independent variables comprised the vulnerability level in the individual, social and programmatic dimensions. Data analyses were performed through logistic re-gression. The results showed a high prevalence of infections (47.3%) and only variables of individual vulnerability were associated with the outcome. The incidence of infection was four times higher among women who had had prior infections. The fact of never having had a blood test tripled the chance of having sexually transmitted infections. The fact of also having sexual intercourse with men in the previous 12-month-period increased the risk of the outcome by a factor of approximate-ly nine. The conclusion drawn is that these women are vulnerable to sexually transmitted infections due to their individual vulnerability.
Vulnerabilidade de mulheres que fazem sexo com mulheres às infecções sexualmente transmissíveis
Keywords: Female homosexuality; Sexually transmitted infections; Vulnerability